PEARL MILLET ACREAGE SUPPLY RESPONSE IN NIGERIA: A NERLOVE ADJUSTMENT MODEL - SEEMA, UMAR S. MAIADUA, K. SUHASINI and (The Journal of Research, PJTSAU, 2019)
Acreage supply response was estimated for pearl millet in Nigeria during the period 1960-61 to 2015-16 using Nerlovian adjustment and price expectation model. The findings revealed that acreage of pearl millet was very low and price inelastic compared to area under cultivation. Similarly, sorghum price and area were significant variables and indicated a complementary relationship with pearl millet, while credit and fertilizer decreased millet area ostensibly due to shift in production. It was inferred from the above that policies during the period of study had favored non price factors for profit motive which spelled badly to food self sufficiency. The study recommended sufficient and timely distribution of inputs (credit, fertilizer improved seed varieties etc), effective pricing policy that would facilitate farming as a business rather than a way of life through creation of commodity board and effective pearl millet value chain.